2019
DOI: 10.7150/jca.31059
|View full text |Cite
|
Sign up to set email alerts
|

Hand Foot Syndrome Has the Strongest Impact on QOL in Skin Toxicities of Chemotherapy

Abstract: Background: Chemotherapy often results in dermatologic toxicities, which decrease quality of life (QOL) of cancer patients. These adverse skin reactions sometimes happen simultaneously. Though previous reports have demonstrated that skin reactions influence QOL, those reports were focused on only one kind of skin toxicity or on the most serious skin toxicity. The aim of this study is to demonstrate the contribution of each skin toxicity to QOL. Methods: This is a cross-sectional study at Kinki Central Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
(54 reference statements)
2
29
0
Order By: Relevance
“…A study performed by Urakawa et al concluded that this AE had a stronger impact on HRQOL compared to other skin toxicities of chemotherapy [27]. Finally, alopecia can be related to conventional chemotherapy, targeted therapy or hormonotherapy and has a clearly negative emotional effect that was reported by Freites-Martinez et al [28].…”
Section: Discussionmentioning
confidence: 84%
“…A study performed by Urakawa et al concluded that this AE had a stronger impact on HRQOL compared to other skin toxicities of chemotherapy [27]. Finally, alopecia can be related to conventional chemotherapy, targeted therapy or hormonotherapy and has a clearly negative emotional effect that was reported by Freites-Martinez et al [28].…”
Section: Discussionmentioning
confidence: 84%
“…Rosen et al 29 addressed this issue, and found that patients on targeted therapies experienced a significantly greater number of CAEs and worse QoL with regards to total Skindex-16 and the emotion subdomain compared with patients on non-targeted therapies. Lee et al 33 also reported that patients on targeted therapy experienced worse QoL by means of DLQI. However, Unger et al 35 did not find differences in QoL between targeted therapy alone and combined targeted therapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…In a clinical trial using EGFRI, Joshi et al 27 reported that skin toxicities, including rash, xerosis, paronychia, and pruritus, adversely affected QoL, and rash was associated with a greater QoL decrease. Lee et al 33 also evaluated the impact of skin problems on QoL in patients treated with anticancer agents and reported that palmo-plantar lesions, papulopustular eruption, and periungual inflammation had the highest impact. Similarly, Urakawa et al 34 found that hand–foot syndrome was a stronger factor in decreasing QoL compared to other skin toxicities of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously reported, hand-foot syndrome was the strongest factor in decreasing QoL so that multi-kinase inhibitors, EGFR-TKI, and capecitabine require careful prevention, early detection, and daily medical care [ 22 ]. In the future, we will conduct a multicenter clinical study in order to verify the contribution of this approach to clinical benefits such as prevention of worsening and prolongation of PFS by targeting patients treated with multi-kinase inhibitors, EGFR-TKI, and capecitabine.…”
Section: Discussionmentioning
confidence: 99%